KREASI KATA DALAM BAHASA INGGRIS - Tumewan, Cynthia (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
ABSTRACT This article entitled â€œKreasi Kata dalam Bahasa Inggrisâ€. Word creation is a process to produce new words. In communication, people use word to express their feelings and to deliver their ideas. In other words, they need words to communicate with others verbally or non-verbally. Communication is a medium to build a relation among people. People use language to do communication. The data which are sentences containing these words have been selected from articles, dictionaries, newspapers, magazines and other linguistic textbooks which discuss about clipping, blending, back formation, acronyming and coinage. The objective of this research is to identify, analyze and describe the words created through clipping, blending, back formation, acronyming, and coinage in English language. Speakers of English sometimes do not know or realize that some words in the vocabulary are originally formed by clipping, blending, back formation, acronyming and coinage. This study would like to suggest to other researchers to study about the other processes of forming words like conversion, derivation, onomatopoeia, proper names and also other processes. Keywords : English, Word Formation, Usage